“It All Makes Us Feel Together”: Young People's Experiences of Virtual Group Music-Making During the COVID-19 Pandemic - Levstek, Maruša; Barnby, Rubie Mai; Pocock, Katherine L.; Banerjee, Robin (Frontiers in Psychology, 2021)
We know little about the psychological experiences of children and young people who have participated in virtual group music-making during the Covid-19 pandemic. Adopting a mixed-methods design, we worked across three music education hubs in the UK, with a total 13 virtual music groups. These included a range of mainstream ensembles, inclusive ensembles targeting young people with special educational needs and/or disabilities, and inclusive music production spaces, targeting young people from lower socio-economic backgrounds. Reported progress in intra- and inter-personal psychological outcomes was investigated using quantitative and qualitative staff session reports, which were collected since before the pandemic (n for in-person sessions = 87, n for virtual sessions = 68), and surveys distributed to tutors, young people, and their parents during the first and second UK national lockdowns (n for qualitative responses = 240, n for quantitative responses = 96). Satisfaction of three basic psychological needs of self-determination theory and their relation to joint music-making in virtual spaces was also observed in real time by the researchers performing quantitative checklist observations on 16 separate occasions. Findings indicated that virtual music groups represented a meaningful psychological resource for the participating children and young people, especially considering the lack of opportunities offered by their schools and other extra-curricular activities. Through their participation with virtual group music-making activities, young people used music as a tool for self-expression and emotion management, restored lost musical identities and confidence, and preserved treasured social connections. Virtual alternatives to group music-making appear to indirectly nurture the sense of belongingness, mediated by supportive staff behaviours, but their direct connection, which has been widely reported for in-person group music-making experiences, has not been observed in virtual music groups.